2009
DOI: 10.2353/ajpath.2009.090037
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Sphingosine 1-Phosphate (SIP)/S1P3 Signaling in Cholestasis-Induced Liver Fibrosis

Abstract: Bioactive sphingosine 1-phosphate (S1P) and S1P receptors (S1PRs) have been implicated in many critical cellular events, including inflammation, cancer, and angiogenesis. However, the role of S1P/S1PR signaling in the pathogenesis of liver fibrosis has not been well documented. In this study, we found that S1P levels and S1P 3 receptor expression in liver tissue were markedly up-regulated in a mouse model of cholestasis-induced liver fibrosis. In addition, the S1P 3 receptor was also expressed in green fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 45 publications
(65 reference statements)
6
80
1
Order By: Relevance
“…Mechanistic studies demonstrate that suramin inhibits apoptosis, suppresses expression of proinflammatory cytokines, inactivates myofibroblasts, and blocks multiple cell signaling pathways . Recent animal studies from our laboratory and by other investigators have shown that administration of suramin can attenuate muscle, liver, and renal fibrosis (Chan et al, 2003;Li et al, 2009;. We have shown that suramin treatment can suppress the expression of fibronectin and a-SMA and type I collagen and reduce the deposition of extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 88%
“…Mechanistic studies demonstrate that suramin inhibits apoptosis, suppresses expression of proinflammatory cytokines, inactivates myofibroblasts, and blocks multiple cell signaling pathways . Recent animal studies from our laboratory and by other investigators have shown that administration of suramin can attenuate muscle, liver, and renal fibrosis (Chan et al, 2003;Li et al, 2009;. We have shown that suramin treatment can suppress the expression of fibronectin and a-SMA and type I collagen and reduce the deposition of extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, the inhibition of those receptors may account, at least in part, for the antifibrotic effect of suramin observed after UUO injury. Nevertheless, suramin is an inhibitor with broad specificity and also inhibits other membrane receptors such as purinergic receptor P2X 7 and sphingosine-1-phosphate receptors (Goncalves et al, 2006;Li et al, 2009). Because these two receptors are also associated with development and progression of tissue fibrosis, it will be interesting to further investigate whether blockade of these receptors by suramin contributes to its antifibrotic effects.…”
Section: Suramin Inhibits Progression Of Renal Fibrosis 763mentioning
confidence: 99%
“…Studies on animal models have shown that administration of suramin attenuates muscle and liver fibrosis (Chan et al, 2003;Li et al, 2009). Furthermore, suramin can prevent coronary restenosis after percutaneous transluminal coronary angioplasty (Urasawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Suramin is also a potent inhibitor for purinergic receptors and sphingosine-1-phosphate receptors. 34,43 Recent studies have shown that the development of renal fibrosis after UUO injury and of hepatic fibrosis after bile duct ligation is associated with P2X 7 and sphingosine-1-phosphate receptors. 44,45 Further investigations are needed to evaluate whether the antifibrotic action of suramin is also associated with inhibition of these two receptors in the kidney.…”
Section: Basic Research Wwwjasnorgmentioning
confidence: 99%
“…31,32 Recent experimental studies showed that it is also effective in attenuating muscle and liver fibrosis. 33,34 However, it remains unclear whether suramin has an antifibrotic effect in the kidney.…”
mentioning
confidence: 99%